2019
DOI: 10.1523/jneurosci.1108-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Firing Rate Homeostasis Can Occur in the Absence of Neuronal Activity-Regulated Transcription

Abstract: Despite dynamic inputs, neuronal circuits maintain relatively stable firing rates over long periods. This maintenance of firing rate, or firing rate homeostasis, is likely mediated by homeostatic mechanisms such as synaptic scaling and regulation of intrinsic excitability. Because some of these homeostatic mechanisms depend on transcription of activity-regulated genes, including Arc and Homer1a, we hypothesized that activity-regulated transcription would be required for firing rate homeostasis. Surprisingly, h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…A hypothesis was tested that the activity dependent transcription necessary for supporting constant activity level (neuronal activity homeostasis); however, homeostasis was observed also in the neurons with the suppressed activity of the plasticity related gene Arc and in the absence of the activity dependent tran scription factors AP1 and SRF. The authors concluded that the activity regulated transcription was not necessary for the constantly maintained activity of the neuron [38].…”
Section: Specificity Of Epigenetic Regulation Of the Plasticity Relatmentioning
confidence: 99%
See 1 more Smart Citation
“…A hypothesis was tested that the activity dependent transcription necessary for supporting constant activity level (neuronal activity homeostasis); however, homeostasis was observed also in the neurons with the suppressed activity of the plasticity related gene Arc and in the absence of the activity dependent tran scription factors AP1 and SRF. The authors concluded that the activity regulated transcription was not necessary for the constantly maintained activity of the neuron [38].…”
Section: Specificity Of Epigenetic Regulation Of the Plasticity Relatmentioning
confidence: 99%
“…Stability of the spontaneous activity of neurons was analyzed in a very interesting work on a culture of mouse cortical neurons [38]. A hypothesis was tested that the activity dependent transcription necessary for supporting constant activity level (neuronal activity homeostasis); however, homeostasis was observed also in the neurons with the suppressed activity of the plasticity related gene Arc and in the absence of the activity dependent tran scription factors AP1 and SRF.…”
Section: Specificity Of Epigenetic Regulation Of the Plasticity Relatmentioning
confidence: 99%
“…For instance, the MFR of a neuronal population gradually renormalizes despite the constant presence of a pharmacological, genetic, or experiencedependent perturbation that initially caused a rapid change in MFR (Figure 1B,C). This process dubbed 'firing rate homeostasis,' occurs robustly in cultured neural networks ex vivo [9][10][11][12][13][14], and has been documented in vivo as well, such as in the rodent primary visual cortex (V1) [15][16][17]. On the basis of these results, MFR can be classified as a physiological variable that undergoes homeostatic set-point regulation.…”
Section: Homeostatic Regulation Of Firing Rate Set Pointsmentioning
confidence: 97%
“…Somatic mitochondria may regulate transcription [59], which is required for synaptic scaling [55]. However, a recent study suggests that transcription is not required for MFR renormalization, at least for Type 1 perturbations related to hyperactivity [14]. Future studies are needed to address whether transcription is unnecessary for inactivity perturbations as well and to understand the role of mitoCa 2+ -transcription coupling in homeostatic regulation.…”
Section: Sleep Homeostasismentioning
confidence: 99%
“…We are only beginning to understand the molecular mechanisms behind these changes. Even fundamental biological phenomena such as the adaptation in electrical excitability in response to the changing synaptic inputs are only beginning to be unraveled [106]. Cellular and animal models of dopamine depletion will be critical to address these questions and hold great promise to develop new non-dopaminergic therapies that have the potential to avoid these long-term consequences of dopamine depletion and substitution.…”
Section: Future Perspectives For Translational Researchmentioning
confidence: 99%